Use of Smartphone in Retrieving Information among PG Students (LIS TODAY, 2021)
We are living in technology era, everyone is using technological devices. Smartphone is also one of  them. Smartphones are providing various applications like internet, e-mail, weather update, academic  related various apps, short message device, video call facilities, current news, access document from  anytime and anywhere and retrieval of information. The smartphone device is working as a multi functional device. The Smartphone is an information gadget for retrieving information for students. It  can also easily portable device. In the other words today, smartphone works like a computer. We can  say that smartphone is a combination of computer. This article related to my Master degree  dissertation work.
Keywords: Information; Information Retrieval; Smartphone